Investigation of Actualization of Learning to Learn Competence in Chemistry Classes - Degutytė-Kančauskienė, Aušra (Acta Paedagogica Vilnensia, 2020)
The object of this study is the learning to learn competence. The purposes of this research are as follows: (1) to highlight the challenges of the actualization of learning to learn competence in science education; (2) to investigate the learning to learn competence of 16–17-year-old students of N gymnasium; (3) to provide conclusions on the learning to learn competence of students and the most relevant aspects of developing this competence in chemistry lessons. The results of a quantitative study (attended by 172 students) confirms the hypothesis that the learning to learn competence closely correlates with learning outcomes. Successful learners are more confident and are more likely to experience satisfaction and a sense of victory; on the other hand, permanent failure can cause poor self-esteem, indifference, avoidance, and aggression. Students with the best grades also have a stronger will and self-discipline to achieve their goals. They also develop this discipline more often than the learners whose learning grades are lower. The results of the survey indicate that all students have a lack of knowledge about different learning methods and the ability to choose the most appropriate ones for specific cases. One of the effective tools that may help a learner successfully comprehend at first sight a rather complicated science – chemistry – is the development of competence-based learning. For this reason, in the paper, together with the challenges of achieving the learning to learn competence, presented by the participants of the study, the possible ways of solving them are described too.